Detection of the ratio error drift in CVT considering AVC. (May 2019) - Zhang, Chuan-ji; Li, Hong-bin; Chen, Qing
Highlights: Detect the ratio error drift of capacitor voltage transformer remotely without power failure. Keeping Valid with the automatic voltage control system. Show better performance than principal component analysis method proposed before. Simulation on field data and experiment in laboratory validates the method. Abstract: With the wide use of the capacitor voltage transformer (CVT), ensuring its accuracy is important. The conventional method is periodical on-site calibration, which is time-consuming and needs the power cut. This paper proposed an on-line method detecting the ratio error (RE) drift based on the correlation between three phase voltages. Considering the widely used automatic voltage control (AVC) system, the independent component analysis (ICA) rather than principal component analysis (PCA) is more suitable to separate the ratio error drift from the load fluctuation. The simulation on field data shows that ICA can detect the drift under AVC whereas the PCA cannot. The laboratory experiment shows the ICA is more sensitive than the PCA.